Das Geheimnis der Gioconda: Das Tagebuch des Diebes - Schwitzky, Ernst Bernhard Joseph Theodor, 1885?- (Salt Lake City, UT : Project Gutenberg, 2013)
"Das Geheimnis der Gioconda: Das Tagebuch des Diebes" by Schwitzky is a fictional narrative written in the early 20th century. The work delves into the mysterious disappearance of the renowned painting, the Gioconda, from the Louvre, presenting a unique perspective through the diary of a thief. The main character, who remains unnamed in the opening portions, becomes enmeshed in a web of intrigue involving a curious man named Daco-Nogi, who has a peculiar fascination with other people's lives. At the start of the story, the narrator recounts a chance encounter with Daco-Nogi in a Copenhagen hotel. Intrigued by this enigmatic figure and his uncanny ability to deduce personal details about others, the narrator becomes increasingly fascinated with him. Upon parting, Daco-Nogi leaves behind a mysterious green folder that contains details about the theft of the Gioconda. As the narrative unfolds, the protagonist contemplates their own life and soon finds themselves drawn into the suspense surrounding Daco-Nogi's intentions, creating a sense of unease as they witness the unfolding events surrounding the imminent heist of one of the most famous artworks in history. (This is an automatically generated summary.)
Release date is 2013-09-15
Produced by Jens Sadowski
Keywords: Art thefts -- France -- Paris -- Fiction; Leonardo, da Vinci, 1452-1519. Mona Lisa -- Fiction